A placebo-controlled study of the doses and efficacy of Lentinula edodes mycelia for oxaliplatin-induced peripheral neuropathy in colorectal cancer - Boku, Shogen; Satake, Hironaga; Mitani, Seiichiro; Maeda, Kiyoshi; Kudo, Toshihiro; Yamaguchi, Toshifumi; Takagi, Tatsuya; Kawakami, Hisato (Frontiers in Oncology, 2025)
IntroductionPreclinical studies have demonstrated the potential of Lentinula edodes mycelium (L.E.M.) extract for managing oxaliplatin-induced peripheral neuropathy (OIPN). The efficacy and optimal dosage of L.E.M. for OIPN remain uncertain. We evaluated the efficacy and safety as well as the optimal dosage of L.E.M. extract for OIPN in patients with colorectal cancer (CRC).MethodsAfter curative resection, we used a 1:1:1 ratio to randomly assign patients with CRC with persistent OIPN (defined by a visual analogue scale [VAS] numbness score ≥40 mm) to the low-dose (L.E.M. 300 mg twice daily [bid]), high-dose (L.E.M. 900 mg bid), and placebo groups. The primary endpoint of this double-blind, placebo-controlled phase 2 trial was the reduction in the VAS numbness score in the low-dose group compared with that in the placebo group at 12 weeks. Adverse events (AEs) and quality of life were evaluated.ResultsForty-five patients were randomly assigned to the placebo (n = 15), low-dose (n = 15), and high-dose (n = 15) groups. At 12 weeks, no significant difference in the reduction of the VAS numbness score was observed when the low-dose and placebo groups were compared (−12.20 [95% confidence interval CI; −34.54 to 10.14] vs. −10.69 [95% CI; −27.07 to 5.69]; p = 0.83); however, the high-dose group showed a favorable trend compared with the placebo group (−12.20 vs. −29.32 [95% CI; −53.4 to −5.2]; p = 0.06). Grade 3 or higher AEs related to the intervention were not observed.DiscussionHigh-dose L.E.M. extract resulted in a clinically meaningful improvement in VAS numbness scores without severe toxicity.Clinical Trial Registrationhttps://jrct.mhlw.go.jp/en-latest-detail/jRCTs051210085, identifier jRCTs051210085.